Numerical analysis of solar updraft power plant integrated with external heat source - Aurybi, M.A. (EDP Sciences, 2017)
Many countries started to adopt clean energy sources, where solar energy is the first priority. Solar chimney power plant was selected in this study as a system which converts solar thermal energy to electrical power. In this research, hybrid solar chimney power plant model has been proposed as a day and night functional integrated system using external heat source to enhance the system performance and cover the setback of solar absence at night and cloudy days. With the help of ANSYS Fluent software, three-dimensional steady-state of Navier-Stokes and energy equations have been solved. Realized k-a two equation turbulent model equations and discrete ordinates (DO) radiation model equations were solved for the conventional model. The results were validated using experimental measurements. Afterward, the influence of thermal enhancing channels installation on the system performance was predicted and analysed in hybrid mode. The simulation results showed that this system could enhance the plant during the day. Percentage of enhancement was 10 and 14 for velocity and temperature respectively, and the power output percentage enhancement was 18 when the solar intensity was 1000 W/m2, and external heat source mass flow rate and the temperature for each channels was 0.015 Kg/s and 100°C respectively, in comparison with the conventional model. © The authors, published by EDP Sciences, 2017.